2014
DOI: 10.18632/oncotarget.2127
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic nexus of cancerous inhibitor of protein phosphatase 2A (CIP2A): An oncoprotein with many hands

Abstract: Oncoprotein CIP2A a Cancerous Inhibitor of PP2A forms an “oncogenic nexus” by virtue of its control on PP2A and MYC stabilization in cancer cells. The expression and prognostic function of CIP2A in different solid tumors including colorectal carcinoma, head & neck cancers, gastric cancers, lung carcinoma, cholangiocarcinoma, esophageal cancers, pancreatic carcinoma, brain cancers, breast carcinoma, bladder cancers, ovarian carcinoma, renal cell carcinomas, tongue cancers, cervical carcinoma, prostate cancers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 118 publications
(143 reference statements)
1
68
0
Order By: Relevance
“…Our hypothesis is that tumors sensitive to PPA inhibition have acquired defects in PP2A activity or regulation that make them more vulnerable to pharmacologic inhibition of PP2A than normal cells. There is a large and growing body of evidence that endogenous inhibitors of PP2A, especially the SET/I2PP2A and CIP2A oncoproteins, are overexpressed in and responsible for reduced PP2A activity in many types of solid tumors and acute and chronic myeloid leukemias (8,(24)(25)(26). Several groups are pursuing pharmacologic means to either inhibit SET or increase PP2A as treatment for such cancers (27)(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis is that tumors sensitive to PPA inhibition have acquired defects in PP2A activity or regulation that make them more vulnerable to pharmacologic inhibition of PP2A than normal cells. There is a large and growing body of evidence that endogenous inhibitors of PP2A, especially the SET/I2PP2A and CIP2A oncoproteins, are overexpressed in and responsible for reduced PP2A activity in many types of solid tumors and acute and chronic myeloid leukemias (8,(24)(25)(26). Several groups are pursuing pharmacologic means to either inhibit SET or increase PP2A as treatment for such cancers (27)(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Some groups focus on identifying potential anti-cancer drugs that inhibit CIP2A expression (e.g., the natural compounds celastrol, ethoxysanguinarine, and fusogenic-oligoarginine peptide), while others investigate CIP2A's role in chemotherapy resistance (among other things, CIP2A mediates the apoptotic effect of bortezomib in hepatocellular carcinoma cells and the synergism between temsirolimus and cetuximab in colon cancer) [29][30][31][32][33][34]. Based on the results of our experiments that demonstrated an association between CIP2A and H-Ras as well as on the previously reported interactions between CIP2A and the c-Myc and Akt signaling pathways, we speculate that CIP2A would be an effective target for cancer therapy [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Huang et al demonstrated that depletion of CIP2A in castration-resistant cancers can sensitize prostate carcinoma cells to therapeutic agents [24]. Since its discovery in 2007, interest in CIP2A as a potential biomarker and/or drug target for the diagnosis and treatment of cancer has steadily increased (reviewed in [25,26]). …”
Section: Introductionmentioning
confidence: 99%